2021
DOI: 10.1093/heapol/czab024
|View full text |Cite
|
Sign up to set email alerts
|

Using WhatsApp messenger for health systems research: a scoping review of available literature

Abstract: Globally, the use of mobile phones for improving access to healthcare and conducting health research has gained traction in recent years as rates of ownership increase, particularly in low- and middle-income countries (LMICs). Mobile instant messaging applications, including WhatsApp Messenger, provide new and affordable opportunities for health research across time and place, potentially addressing the challenges of maintaining contact and participation involved in research with migrant and mobile populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 55 publications
0
30
0
1
Order By: Relevance
“…Since the main aim of this study is to test the implementation of the intervention, outcome measures such as iFOBT completion and colonoscopy attendance will be used to report on the appropriateness and feasibility of the intervention. WhatsApp is used increasingly for research purposes in LMICs, mainly to share links to online surveys 37 and it is the most commonly used platform for personal contact and exchange in Malaysia. We will communicate via text message to participants who do not have WhatsApp.…”
Section: Discussionmentioning
confidence: 99%
“…Since the main aim of this study is to test the implementation of the intervention, outcome measures such as iFOBT completion and colonoscopy attendance will be used to report on the appropriateness and feasibility of the intervention. WhatsApp is used increasingly for research purposes in LMICs, mainly to share links to online surveys 37 and it is the most commonly used platform for personal contact and exchange in Malaysia. We will communicate via text message to participants who do not have WhatsApp.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, social media networks, especially Facebook, are now commonly used in medical research, specifically for cross-sectional design, and many studies have demonstrated its usefulness for quickly recruiting a large sample at the lowest cost [ 92 , 93 , 94 ]. Concerning other social media, although they are a little more recent than Facebook, their use is becoming more and more democratized in new studies, especially Instagram [ 95 , 96 ] and WhatsApp [ 97 , 98 ]. At the same time, we required that the respondents should be at least 18 years old to participate and asked for confirmation from each respondent.…”
Section: Methodsmentioning
confidence: 99%
“…There is a growing body of literature that recognizes the affordances of smartphone devices and messaging apps for data collection and participant interaction in qualitative research (de Gruchy et al, 2021;Manji et al, 2021). A significant analysis and discussion on the subject were presented by Kaufmann et al (2021;Kaufmann & Peil, 2020).…”
Section: Using Mobile Messaging Apps As a Tool For Data Collectionmentioning
confidence: 99%
“…), or commenting on the content they shared in the group chat. Similar to other studies (de Gruchy et al, 2021;Manji et al, 2021), we needed to consider the limitations of data collection and sharing using WhatsApp in research with low socioeconomic status populations. It became clear that some choices when it comes to sharing are related to internet capacity, which may constrain the availability of data for analysis in ways that cannot be predicted.…”
Section: Weaknesses In Using Whatsapp As a Tool For Data Collection A...mentioning
confidence: 99%